1992
DOI: 10.1192/pb.16.8.468
|View full text |Cite
|
Sign up to set email alerts
|

Communication between general practitioners and psychiatrists

Abstract: The quality of care which patients receive within the NHS is dependent upon the communication between general practitioners (GPs) and specialists and the letter is the most widely used instrument in this process (Freeling & Kessel, 1984). There are only a few studies which have evaluated the efficiency of communication between the GP and the hospital specialist. For example, de Alarcon et al (1960) showed that 96% of specialists' reports to GPs were found to offer a definite contribution to the understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Prasher et al (1992) showed that 68% of GPs listed medication on referral of 270 people to out patient departments, while 95% of psychiatrists listed drugs in their reply-drug records were not compared.…”
mentioning
confidence: 99%
“…Prasher et al (1992) showed that 68% of GPs listed medication on referral of 270 people to out patient departments, while 95% of psychiatrists listed drugs in their reply-drug records were not compared.…”
mentioning
confidence: 99%
“…A recent study showed that such information is contained in approximately 50% of referrals except for 'reason for referral', which is contained in 87Yn (Prasher et al, 1992). Old age psychiatrists may expect different information from GPs to reflect the increased incidence of physical illness and cognitive impairment in elderly compared to adult patients.…”
mentioning
confidence: 95%
“…There is some evidence of a link between the appropriateness of referral and the quality of infomation contained in the referral letter (Jenkins, 1993). Several studies exist examining the quality of referrals between GPs and adult psychiatrists (Pullen and Yellowlees, 1985;Wilkinson, 1989;Prasher et al, 1992) and between GPs and child psychiatrists (Kentish et ul., 1987;Cornwall, 1993) but no study has systematically looked at the quality of information in GP referrals to old age psychiatrists.There are studies which look at what hospital specialists in general expect from GP referrals (Newton et al, 1992) and for adult psychiatric patients (less than 65 years old) it has been suggested that referrals should contain information on reason for referral, main symptoms, past psychiatric history, medication and family history (Pullen and Yellowlees, 1985). A recent study showed that such information is contained in approximately 50% of referrals except for 'reason for referral', which is contained in 87Yn (Prasher et al, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly so if there is a question of psychotherapy, cognitive-behavioural therapy, other psychological therapies or, especially, counselling. Prasher et al (1992), studying communication between GPs and psychiatrists, found that GPs prefer letters from psychiatrists that are one page in length and have only two or three subheadings, but psychiatrists appear to prefer to write longer letters which follow the Institute of Psychiatry guidelines. Psychiatrists' letters varied from a minimum of A4 length to a maximum of three sides of A4.…”
Section: Communication Between General Practitioners and Psychiatristsmentioning
confidence: 99%